Telaah Fatwa tentang Nikah Siri - Faishal Agil Al Munawar (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2020)
This research discusses about Fatwa regarding Siri Marriage or known as Unregistered Marriage. In the other countries, this phenomenon called ‘Urfi Marriage. This research comprised in normative category because analyzing documents and literatures related to Fatwa regarding Siri Marriage. Qualitative Description is used as an approach to compare between Indonesian Ulema Council or Majelis Ulama Indonesia (“MUI”) with other five Fatwa councils from different countries: (1) Kingdom of Saudi Arabia (“KSA”), (2) Egypt, (3) Jordan, (4) Kuwait, and (5) Libya. The results show that in substance and procedure, Siri or ’Urfi Marriage activities in five nations are indifferent. The distinction only occurs on the naming aspect. Indonesia and KSA have the same terminology which is Siri Marriage, whereas three other countries employ ‘Urfi Marriage expression. From legal perspective, those five nations have similar concept that, if the marriage complies with the Islamic basis and requisite, then it fulfills legitimate sharia condition for marriage in Islam. But, to accomplish rights in civil law, it needs to register the marriage officially in the country’s appointed institution.